2019
DOI: 10.1038/s41598-019-43121-w
|View full text |Cite
|
Sign up to set email alerts
|

Publisher Correction: Protein expression changes caused by spaceflight as measured for 18 Russian cosmonauts

Abstract: A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A recent study showed an increase in osteocyte senescence after irradiation [ 17 ]. Although PPIA has been identified as a very stable and GAPDH as fairly stable reference genes during in vitro senescence in mesenchymal stem cells [ 18 ], it is noteworthy that GAPDH expression decreases during in vivo aging in fibroblasts [ 19 ]. As in vivo molecular mechanisms of irradiation-induced osteocyte senescence have not been fully elucidated yet, we strongly suggest interpreting possible differences between group C and C irrad carefully.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed an increase in osteocyte senescence after irradiation [ 17 ]. Although PPIA has been identified as a very stable and GAPDH as fairly stable reference genes during in vitro senescence in mesenchymal stem cells [ 18 ], it is noteworthy that GAPDH expression decreases during in vivo aging in fibroblasts [ 19 ]. As in vivo molecular mechanisms of irradiation-induced osteocyte senescence have not been fully elucidated yet, we strongly suggest interpreting possible differences between group C and C irrad carefully.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, these proteins do not return to pre-flight baselines by day 7 after spaceflight. They are involved in the blood clotting system, ECM remodeling, and immune processes [ 104 ].…”
Section: Proteomic Profile Of Human Matrisome-associated Proteins Under Real and Simulated Microgravitymentioning
confidence: 99%
“…Latridis et al suggest that these reactions may be triggered by extracellular signaling pathways of mechanotransduction [ 105 ]. Part of the group of functionally ECM-associated proteins detected in the samples at day 1 after landing in a reduced concentration, were found to return to baseline after 7 days, but another part of proteins retained significantly reduced concentrations [ 103 , 104 ]. The ANDCell program made it possible to identify biological processes involving ECM proteins that are modified by spaceflight factors ( Table 2 ).…”
Section: Proteomic Profile Of Human Matrisome-associated Proteins Under Real and Simulated Microgravitymentioning
confidence: 99%